2017
DOI: 10.14260/jemds/2017/306
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Analysis of Validity of Lateral Placental Location in Prediction of Preeclampsia

Abstract: BACKGROUNDAim of the study is to analyse whether placental location as determined by ultrasound at 18-24 weeks can predict the subsequent development of preeclampsia. MATERIALS AND METHODSThis study was conducted in 300 women at the Department of Obstetrics and Gynaecology for a period of one year. The location of placenta was determined by ultrasound at 18-24 weeks of gestational age in the study population. The placental position was being classified as central, right/left. Prospectively case group and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…In this study by Kannamani et al 81% were primigravidae. 14 In our study, the incidence of preeclampsia was 19.34% which is higher compared to Rodriguesz et al 10.6%, Kumar et al 13.6% and Ramos et al reported as 14%. [23][24][25] Pre-eclampsia here is common in extremes of age group.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In this study by Kannamani et al 81% were primigravidae. 14 In our study, the incidence of preeclampsia was 19.34% which is higher compared to Rodriguesz et al 10.6%, Kumar et al 13.6% and Ramos et al reported as 14%. [23][24][25] Pre-eclampsia here is common in extremes of age group.…”
Section: Discussioncontrasting
confidence: 50%
“…Infants of women with severe preeclampsia have 5-fold increase in mortality compared to infants of normotensive women. 14 Non-invasive doppler velocimetry studies of uterine arteries in second trimester reveal abnormal waveforms suggestive of defective uterine perfusion due to placental implantation. 1 Placental location can be documented by various means, but ultrasound has proved to be safest, easiest and most accurate method.…”
Section: Introductionmentioning
confidence: 99%
“…10 Kannamani and Narasimhan showed that placental position as determined by ultrasound between 18-20 weeks of gestation is an excellent screening test with a very high sensitivity. 11 The present study was done to know if there is any correlation in lateral placental location with preeclampsia; and maternal and fetal outcome.…”
mentioning
confidence: 97%